Amentoflavone for treating cardiocerebrovascular diseases and neurological disorders - Zhang, Hang; Ban, Yin-mei; Li, De-mei; Wang, Gang; Gu, Juan; Zhu, Lei (Frontiers in Pharmacology, 2024)
Amentoflavone (AME) is a flavonoid compound found in over 120 plants. Its extensive pharmacological activity for treating cardiocerebrovascular diseases and neurological disorders have attracted the attention of researchers in recent years.However, owing to the poor solubility and low bioavailability of AME, it has not been developed as a drug for treating these diseases. This review focuses on two aspects of AME: First, it provides a detailed summary and introduction to AME based on its chemical structure, physicochemical properties, plant sources, extraction and purification methods, administration systems, and pharmacokinetic properties. Second, it summarizes the effects of AME on cardiocerebrovascular diseases and neurological disorders, and its specific pharmacological mechanisms. This review aims to promote the use of AME for treating cardiocerebrovascular diseases and neurological disorders. AME exhibits multiple activities, indicating its potential as a natural drug for treating these diseases. Further studies on its pharmacokinetics and toxicology are required to ensure its safety and efficacy.